Development of a modified paediatric coma scale in intensive care clinical practice. Issue 6 (1st December 1997) - Tatman, A; Warren, A; Williams, A; Powell, J E; Whitehouse, W
Abstract : James' adaptation of the Glasgow coma scale (JGCS) was designed for young children. Intubated patients are not allocated a verbal score, however, so important changes in a patient's conscious level may be missed. A grimace score was therefore developed and assessed for use in intubated children. Two observers made a JGCS observation within 15 minutes of each other. One observer was the patient's nurse and the other a trained investigator. Interobserver reliability was determined between the first and second observation for each component of the scale. Reliability was measured using κ and weighted κ statistics. Seventy three children had 104 sets of observations. Interobserver reliability was moderate to good for all components, with the grimace score better than the verbal score. It is concluded that the grimace score is more reliable than the verbal score and may be useful in intubated patients in whom the verbal score cannot be used.